Bound states from the spectral Bethe-Salpeter equation - Eichmann, Gernot; Gómez, Andrés; Horak, Jan; Pawlowski, Jan M.; Wessely, Jonas; Wink, Nicolas (Physical review, 2024)
We compute the bound state properties of three-dimensional scalar 𝜙4 theory in the broken phase. To this end, we extend the recently developed technique of spectral Dyson-Schwinger equations to solve the Bethe-Salpeter equation and determine the bound state spectrum. We employ consistent truncations for the two-, three- and four-point functions of the theory that recover the scaling properties in the infinite coupling limit. Our result for the mass of the lowest-lying bound state in this limit agrees very well with lattice determinations.
Gesehen am 25.11.2024